Investigating the Impact of GGBS and FA as Partial Replacements and PVA Addition on Mechanical Properties of Cement Mortar - Flayyih, Ali; Owaid, Khalid (Journal of Engineering and Technological Sciences, 2026)
This study investigated the effects of partial cement replacement with Fly Ash (FA) and Ground Granulated Blast-furnace Slag (GGBS), as well as the addition of Polyvinyl Alcohol (PVA), on the mechanical and hardness properties of mortars. Mortar mixes were prepared with 15-30% FA (F-series), 15-30% GGBS (G-series), and varying PVA additions (P-series), and compared against a reference mix (Ref). Compressive, tensile, and flexural strengths at 28 days, along with Shore D hardness, were evaluated. Results indicated that both FA and GGBS improved 28-day compressive strength over the reference (Ref: 27.43 MPa), with optimal replacements at 20% FA (F20: 30.02 MPa) and 25% GGBS (G25: 34.12 MPa). GGBS mixes generally outperformed FA mixes across all tested properties, attributed to GGBS's higher calcium content promoting faster hydration and denser C-S-H gel formation. The addition of PVA further enhanced mechanical performance, with the P1 mix achieving the highest compressive (36.76 MPa), tensile (2.76 MPa), and flexural (5.43 MPa) strengths, likely due to PVA's film-forming and crack-bridging capabilities. However, excessive PVA addition showed diminishing returns. All modified mortars exhibited increased hardness compared to the reference, with GGBS (G30: 94.11) and PVA (P1: 93.73) mixes showing peak values. The findings highlight the effectiveness of GGBS as a supplementary cementitious material and demonstrate the significant potential of PVA modification for enhancing mortar strength characteristics, although optimal dosages are crucial.